Respostas
respondido por:
3
x² + 6x + 9 = 0
\/.............\/
x..............3
x . 3 . 2 = 6x
x² + 6x + 9 = 0
(x+3)² = 0
x+3 = 0
x = -3
\/.............\/
x..............3
x . 3 . 2 = 6x
x² + 6x + 9 = 0
(x+3)² = 0
x+3 = 0
x = -3
respondido por:
2
x² + 6x + 9 = 0
x² + 3x + 3x + 9 = 0
x(x + 3) + 3(x + 3) = 0
(x + 3).(x + 3) = 0
x + 3 = 0
R.: x = - 3
x² + 3x + 3x + 9 = 0
x(x + 3) + 3(x + 3) = 0
(x + 3).(x + 3) = 0
x + 3 = 0
R.: x = - 3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
a) x²+6+9=0
b) x²+8x+16=36
c) x²+8x-9=0
d) x²+4x-21=0
e) x²-4x-12=0
f) 4x²-8x-12=0
g) 9y²-3y-2=0